AUDIOBOOK FOR INCLUSIVE STUDENTS: ITS EFFECTIVE PRACTICE - Amalia, Rizki; Istiqomah, Faizatul (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
The purpose of this study is to describe audiobook as learning media and todescribe factors influencing the successful used of audiobook by the blind studentsin inclusive school. This study was conducted at MA Muhammadiyah 1 Ponorogo.The instruments were observation, interview, and documentation. The result ofthis study revealed that the process of the use audiobook for supportingreferences in learning English, the teacher introduces an audio application andthen installing it on a blind students’ hand phone or laptop. The factor influencingthe successful use of audiobook by the blind students there are two factors thatare internal and external factor. Internal factor that influencing the success ofblind students in English learning by using audiobook the existence of enthusiasmfrom within. External factor that from parents, teacher, caregivers, and also theirfriends. All of them always help the blind students when needed.